Emergency obstetric referrals in public health facilities: A descriptive study from urban Maharashtra, India - Das, Sushmita; Patil, Sarita; Pathak, Sweety; Chakravarthy, Sahana; Fernandez, Armida; Pantvaidya, Shanti; Jayaraman, Anuja (Frontiers in Health Services, 2023)
Background An effective referral system is key to access timely emergency obstetric care. The criticality of referrals makes it necessary to understand its pattern at the health system level. This study aims to document the patterns and primary reasons of obstetric case referral and the maternal and perinatal outcome of the cases in public health institutions in select areas of urban Maharashtra, India. Methods The study is based on the health records of public health facilities in Mumbai and its adjoining three municipal corporations. The information on pregnant women referred for obstetric emergencies was collected from patient referral forms of municipal maternity homes and peripheral health facilities between 2016 and 2019. Maternal and child outcome data was obtained from “Received-In” peripheral and tertiary health facilities to track whether the referred woman reached the referral facility for delivery. Descriptive statistics were used to analyze demographic details, referral patterns, reasons of referrals, referral communication and documentation, time and mode of transfer and delivery outcomes. Results 14% (28,020) women were referred to higher health facilities. The most common reasons for referral were pregnancy-induced hypertension or eclampsia (17%), previous caesarean section (12%), fetal distress (11%) and Oligohydramnios (11%). 19% of all referrals were entirely due to unavailability of human resources or health infrastructure. Non-availability of emergency Operation Theatre (47%) and Neonatal Intensive Care Unit (45%) were the major non-medical reasons for referrals. Absence of health personnel such as anaesthetist (24%), paediatrician (22%), physician (20%) or obstetrician (12%) was another non-medical reason for referrals. Referring facility had a phone-based communication about the referral with the receiving facility in less than half of the cases (47%). 60% of the referred women could be tracked in higher health facilities. Of the tracked cases, 45% women delivered via caesarean section. Most of the deliveries (96%) resulted in live birth outcomes. 34% of the newborns weighed less than 2,500 grams. Conclusion Improving referral processes are critical to enhance the overall performance of emergency obstetric care. Our findings emphasize the need for a formal communication and feedback system between referring and receiving facilities. Simultaneously, ensuring EmOC at different levels of health facilities by upgradation of health infrastructure is recommended.